ANALISIS STRATEGI PENINGKATAN KUALITAS PELAYANAN PADA HOTEL TIMIKA RAYA - Stepanus Sandy; Asmaul Husna, Neng Silly Mulyadi (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine strategies for improving service quality at the Timika Raya Hotel. The research method used is descriptive, which is a type of research that aims to describe or describe an incident or event. The descriptive method in this research was used to provide an overview of the strategy for improving service quality at the Timika Raya Hotel. In this research, the data collection techniques used were questionnaires and interviews. To find out what the hotel improvement strategy is, the analysis used in this research is a combination of Importance Performance Analysis (IPA) and Strength Weakness Opportunity Threat (SWOT). Based on the results of the Importance Performance Analysis (IPA), the results of the research show that there are attributes included in quadrant A which are the main priority improvements that must be made by the Timika Raya Hotel to meet customer expectations because these attributes are important for hotel customers but are still not in accordance with customer expectations. Based on the results of the SWOT Analysis, the condition of the Timika Raya Hotel is in quadrant I, where the strategy that must be implemented when facing this situation is to support aggressive growth policies